Penerapan Program Bank Sampah untuk Mengatasi Masalah ISPA Akibat Pembakaran Sampah di Desa Karyamukti Kota Banjar Tahun 2025 - Siti Fatimah; Syahla Rahmah Ainun Nisa; Riana Pramuji; Neng Dila Husnunisa; Devina Tiara Safitri; Zahra Bilqis Syahidah; Marshanda Darianti; Raisa Azkia Utami; Syifa Rahmawati; Nazwa Rahmadina Ghinastirar; Muhammad Defrian Muldani; Rifa Ajrina Faisal; Andik Setiyono (Jurnal Kabar Masyarakat, 2025)
This community service program aims to raise awareness among residents of RW 04 Dusun Cigadung, Desa Karyamukti, about proper waste management. Through the waste bank program, the community is encouraged to sort and recycle inorganic waste, turning it into an economic asset. The methods used include participatory dialogue, socialization, training, and partnerships with the Central Waste Bank. The results indicate an increase in community understanding of waste management, the establishment of a waste bank management structure, and active participation of residents in collecting and weighing waste. This program is expected to be sustainable and serve as a solution to reduce environmental pollution while improving community welfare.